Research and practice of 5G edge cloud based port unified communication scheme - Yan NING; Lei ZHANG; Xiaoyuan LU (Dianxin kexue)
With the advantages of distribution, flexible networking, rapid deployment, and local data offloading, 5G edge cloud has a wide range of application prospects in the vertical industrial field such as ports, and also puts forward certain requirements for the realization of unified communications in ports.On the basis of studying the unified communication architecture of ports based on 5G edge cloud, a functional framework of the 5G edge cloud that realized a comprehensive perception of various elements of the port site and supported the transformation of automated services was proposed.The functional framework could be well applied to the unified hosting of wired and wireless network integration in port scenarios, and could be used as the network infrastructure of unified communication of port networks in the current complex environment.Finally, the scheme was applied to a port terminal for practical verification.